SPORTS FACILITIES IN HIGH-DENSITY URBAN AREA - Wong, Si Weng (University of Saint Joseph, 2023)
How can we provide more sports areas in a high-density urban environment? Nowadays, most cities in Asia are experiencing high-speed development (Satterthwaite, 2023). There is an intensely increasing demand for land that is confronted with an insufficient supply of space, resulting in a shortfall of suitable construction space to meet the rising demand. Over the past few decades, different countries and cities have created various solutions for this issue. This shortage of space has been resolved in various ways, for example: through land reclamation, renovation, and architectural design (Grydehoj, 2015). This dissertation seeks to analyse and discuss how architects have used design to expand spaces within the limited available areas for public spaces like sports facilities (Carmona, 2021). Understanding how sports modalities influence architecture and space utilisation for sports activities will also be covered. Additionally, it will examine case studies on how to better implement the program in a limited urban area with regards to the typology connections of sports facilities and their interaction with users. Finally, this dissertation is practice-based and oriented, the case study and project development will focus on a sports facility in the high-density populated Taipa Centre (Macau). This specific project solution will address the real problem for the city, and research will conclude by analysing the constraints of sports architecture in high-density areas, providing design solutions for these situations, and thereby contributing to the improvement of public spaces in a city
Keywords: Centrality; High-Density Urban Spaces; Indoor-Outdoor Interaction; Sports Facilities; Stacking; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

UNITING - FRAGMENTED SPACES ARCHITECTURE CENTRALIZING HERITAGE INTERPRETATION - Un, Cheng Wai (University of Saint Joseph, 2023)
For many people, an art museum is a place to display artifacts, artworks, and the temporaryhistory of a community or country. It also advocates for an artist’s viewpoints on art. In fact,museum design is closely related to politics. The purpose for building a museum in a city is toexhibit information about the development of the local culture. Moreover, high culturalvalue land is usually built with museums displaying their heritage nearby, so that people canexplore and learn more about the local historical background and artifacts of the place.The abandoned Iec Long Firecracker Factory in Taipa Center, Macau has been on hold formany years and has also been used as a war game venue that resulted in scratches on thewalls of the dilapidated old heritage buildings. Recently, the Macau government has finalizedits plans for the revitalization of this local heritage site. Due to its dispersed layout andsurrounding landscape, there are some design constraints around the preservation of thisimportant heritage site. The design for high cultural value land should not only consider thepreservation and renovation of old buildings but also consider more ways to effectively usethe site as an important public venue for the city.For developing the methodologies of this project, several concepts and case studies wereanalyzed to extract ideas that can be referenced and to unveil strategies for designing apossible solution to this problem. This dissertation intends to create a model for developingand integrating architectural design into this heritage site and will study the spacearrangements for both the indoor space and the outdoor space within the concept of afragmented space integration. Fragmented space, means that a place is designed using adecentralized layout. This conceptualization of a design can preserves the original appearance of the cultural value of land and at the same time, the space can be used moreefficiently to create a circulation for the public to visit and enjoy the location
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; articulation architecture; decentralized layout; functional museum; integration with architecture; spatial narrative

CUSTOM CLUSTER: DEMAND-DRIVEN VERTICAL HOUSING ARCHITECTURE - Un, Ka Kin (University of Saint Joseph, 2023)
Vertical housing is essential for modern cities because of its efficiency in using space (Wang, J. Murakami, A. 2019). The architecture of vertical housing is often determined by developers and designers. Therefore, the architecture of the building is fixed, and the end users are not involved nor can they influence its final appearance. For residential buildings, the unit sizes are based on market demand at a given point in time, which does not reflect the dynamic needs of the population as they evolve and may result in a mismatch between the supply and the demand for housing. The design of housing towers that have demographic characteristics and family size is dependent on housing size and can be very uncharacteristic and repetitive. The research question identified and addressed in this study is: How can residential buildings meet the evolving demand for housing units? Based on this question, this research paper develops a prototype for residential to resolve the dilemma between the supply and the demand in terms of the apartment size and layout. This research is a project-oriented project that focuses on residential that reflects the different family sizes required to be housed in the building and is combined with the open building method to maximize building performance. Ultimately, this research represents a meaningful innovation for market-driven architecture and defines architectural design based on the changing needs of the population using the open construction method. It also provides an opportunity to improve the design efficiency and develop a method for future growth, upgrades, and user needs. It may also be able to reflect the current housing ratio of the residential building. This work can be further explored to verify its effectiveness for other housing types and community living spaces
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; Vertical residential design; demand-driven architecture; form follows function; open building; residential clusters; stacking design

Plugin Program Reconfigurable Architecture System For Sustainable Future - Au Yeung, Kam Sheung (University of Saint Joseph, 2023)
The primary research focus of this dissertation revolves around the concept of a "plugin" program. It raises a fundamental question about whether a building can attain long-term usability through metabolic flexibility (plugin units and their reconfigurable space), promoting adaptability (accommodating various program transfers), and meeting sustainable future criteria. Specifically, this dissertation inquires whether this "plugin" building design, with its reconfigurable units and metabolic system, can adapt to different spatial programs and become sustainable architecture
Keywords: Building program transfer; Metabolism Architecture; Plugin capsule units; Reconfigurable; Sustainable Architecture; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph